Electrostatic Sensor in Circular and Rectangular Shape Electrode for Solid Dry Pneumatic Conveyor System - Mohd Riduwan, Ghazali (2011)
The electrostatic sensor was used in industrial process because of less expensive and robust design. The particles movement in pneumatic conveying system can generate the electrostatic charges. The charges can be detected by using the sensing devices such as electrodes or plates. The electrodynamics transducer or associated electronics circuit on the sensing device was used to convert the charge to the voltage. The sensing device was built from conductor and insulator materials that have the different size and shape. Three types of electrodes that commonly used were pin, quarter ring and ring shapes. This paper focuses on pin shape with variation of size for circular and rectangular shapes. Non-intrusive method was designed and applied to the both shapes to investigate the sensitivity of the sensor.